Effect of the Inductive Load on the Capacitance Requirement of Self-Excited Induction Generator (The International Journal of Engineering & Information Technology (IJEIT), 2024)
In this paper, a simple and direct analytical method is proposed to analyze the effect of the load inductance to obtain the minimum requirement of the capacitance for self-excited induction generator for different speeds. A computer software has been developed to compute the minimum capacitance requirement at different load conditions for excitation of the machine for wide range of speeds. Results are compared and discussed in detail..